Rethinking Art, Design, and Cultural History for the Indonesian Design Education and Creative Economy - Kurniawan, Michael Nathaniel (Humaniora, 2019)
This research used extensive literature reviews of the history of Design HE, Art and Design History, Creative and Cultural Industries, Cultural Heritage Studies, and Design Studies to rethink the history, concepts, and common teaching practices of Art, Design, and Cultural History within the Design HE curriculum, especially for the Visual Communication Design Undergraduate program as it contributed to almost all of the creative industries’ sub-sectors. It is discovered that since the Industrial Revolution, the Design HE, the art and cultural museum, and the economy actually shares a strong correlation that has long been rejected and mostly forgotten. Exploring this correlation helps to determine the role of cultural heritage in the creative economy and to position Indonesian cultural heritage as central in the design curriculum. On this account, Art, Design, and Cultural History subject(s) should encourage designers to create new designs as active efforts to preserve past cultural values that also function as creative and critical interventions towards the global creative economy phenomenon.